Blind devotion, violence and trauma in the works of Ka Maiga, Bassek and Mpoudi-Ngolle (2012)
African women, for too long, have been made to exist in the shadow of African men. Their subordination to men has been mostly achieved by the enactment of societal laws in pre-colonial, colonial and neocolonial African settings which categorize them (women) as the other. The consequence of this subjugation is women’s dependence on/and blind acceptance of their inferiority to men. To change the status quo, African feminist writers and critics alike have raised awareness in women about the obduracy of (oppressive tendencies of some African cultural mores. These cultural (ethos /practices are those that spring from essentially controlling woman’s body that practically translate into controlling her mind in order to make her believe the myth that she is inferior to her male (counterpart; The reification of the female body invariably leads to African women’s blind devotion to their husbands, children and most often, the extended family. Besides, women are also victims of male violence and trauma as evidenced in the works of Philomene Bassek, Aminata Ka MaTga and Evelyne Mpoudi Ngolle.